CAUSALITY RELATIONSHIP OF POVERTY, UNEMPLOYMENT RATE, AND ECONOMIC GROWTH IN SOUTH SULAWESI PROVINCE - Akhmad, Akhmad; Marsuni, Nur Sandi (Jurnal Ekonomi Balance, 2019)
Economic development basically aims to increase economic growth, reduce poverty and unemployment. Therefore the research aims to find out the causal relationship between economic growth, unemployment and poverty in the Southern Province. This research used panel data of 24 districts / cities in South Sulawesi Province during 2007 to 2018, which was obtained from the Central Statistics Agency. Data were then analyzed using Vector Autoregression analysis. The results showed that shocks to economic growth have an impact on reducing unemployment and poverty rates both short and long term. Meanwhile shocks to unemployment, have an impact on increasing poverty rates in the short and long term, and have an impact on declining economic growth in the short term, but slowly economic growth returns to the balance point. Furthermore, the shock to poverty also has an impact on increasing unemployment in the short term, but slowly leads to a point of convergence in the long run. It is better to make economic growth decrease in the short term, but slowly towards the point of balance in the long run.